PERAN KODESISETO TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA - Budiman, Arifiansya; Yulinda, Yulinda; Oktriani, Indah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2020)
Abstract— The background of this research originated from the assumption that social science subject is less important, the use of media and teacher methods which are less varied and the low learning activities of students which have an impact on low learning achievement especially for social science subjects. One of the social science teacher's creativeness in delivering material in a varied way is using kodesiseto, which is an acronym from comics with students as figures (komik dengan siswa sebagai tokoh). Comics as an alternative visual media, can be used as illustrations in learning. This media is quite unique and it is expected to make the students become more interested in learning social science so that the learning objectives will be achieved therefore the learning achievement will increase. Besides, the teaching and learning process will be more varied. This research was a classroom action research conducted in class VII.2 SMP Negeri 9 Prabumulih because it had the lowest social science achievement compared to other classes. The results showed that the use of kodesiseto in social science learning could improve students' social science learning achievement as proved by the average pre-test scores in the first cycle were 5.44 then increased to 6.77 on the post-test, the average pre-test scores of students in the second cycle were 6.11 increased to 7.74 in the post test, in third cycle the average value of pre-test and post-test students also increased by 6.92 to 8.66. Thus, the use of kodesiseto can be used as an alternative learning media in social science learning to improve learning activities and students’ achievement in social science subject  Keywords— Kodesiseto, Learning achievement, Social science Abstrak— Latar belakang penelitian ini berawal dari adanya anggapan pelajaran IPS yang kurang penting, penggunaan media dan metode guru yang kurang bervariasi serta rendahnya aktivitas belajar siswa yang berdampak pada rendahnya prestasi belajar terutama pelajaran IPS. Salah satu kreativitas guru IPS dalam penyampaian materi agar bervariasi yaitu dengan menggunakan kodesiseto, yang merupakan akronim dari komik dengan siswa sebagai tokoh. Komik sebagai media visual alternatif, dapat digunakan sebagai ilustrasi dalam pembelajaran. Media ini cukup unik dan diharapkan siswa lebih tertarik dalam mempelajari IPS sehingga tujuan dari pembelajaran IPS akan tercapai serta prestasi belajarnya akan meningkat. Selain itu proses belajar mengajar akan lebih bervariasi. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan di kelas VII.2 SMP Negeri 9 Prabumulih karena memiliki prestasi belajar IPS paling rendah dibandingkan kelas lainnya. Hasil penelitian menunjukkan bahwa  penggunaan kodesiseto  dalam pembelajaran IPS dapat meningkatkan prestasi belajar IPS siswa terbukti dengan rata-rata nilai pre tes pada siklus I sebesar 5,44 meningkat menjadi 6,77 pada post tes, nilai rata- rata pre tes siswa pada siklus II sebesar 6,11 meningkat menjadi 7,74 pada post tes, pada siklus III nilai rata-rata pre tes dan post tes siswa juga  mengalami peningkatan sebesar 6,92 menjadi 8,66. Oleh karena itu penggunaan kodesiseto dapat  dijadikan  alternatif  dalam  pembelajaran  IPS    agar  dapat  meningkatkan aktivitas belajar serta prestasi siswa dalam pelajaran IPS Kata Kunci— Kodesiseto, Prestasi belajar, Ilmu pengetahuan sosial